SUBSTANCE ABUSE PREVENTION: EDUCATIONAL VERSUS BEHAVIORAL INTERVENTION - Caballero Blaya, María; Maciá Antón, Diego (Anales de Psicología / Annals of Psychology)
The main objective of the present research was to prevent and/or to postpone the start on the drug-taking (mainly tobacco, alcohol, medicines and cannabis) in non usual drug-takers seventh level of E.G.B. students. For that, two types of intervention were tested: Educational (formation-attitude change) versus Behavioral (Stuctured Social Skills Training). We have studied these variables: the information about different drugs, the drug-taking habits, the subjects attitudes toward drugs, the social skills to resolve properly the first offer in drug-taking situations, and the free time alternatives contrary to drug-taking. The intervention with the students showed to be more efficiency of Behavioral Program than the Educational Program and Control Group in the majority studied variables.